MOTIVATING THE STUDENTS TO READ ENGLISH MATERIAL BY USING FAIRY TALES OF THE EIGHTH YEAR STUDENTS AT SMP NEGERI 3 POLEWALI - Muthmainnah Muthmainnah (UIN Alauddin Makassar, 2017)
AbstractThe objective of this research is to find out the students’ motivation in reading English material by using fairy tales. In this study, the researcher applied the descriptive method. The population of the research was the eighth year students of SMP Negeri 3 Polewali academic year 2012/2013 which consisted of 4 classes with 124 students. Because the number of students was large enough in number, the writer used random sampling method. The researcher took only 20 students as respondents. The instrument used to gather the data was questionnaire. The data from questionnaires were analyzed by frequency and percentage technique. The result of the data analysis shows that the Eighth year students of SMP Negeri 3 Pelewali have high motivation in reading English material by using Fairy Tales. It can be seen by the data obtained from the questionnaire in table 1 up 19 where shows that the average percentage of students who chosen very interesting is 43% and the students who chosen interesting is 48%. So, the total is 91%. It means that the students who chosen very interesting and interesting greater than 50%. From the data collected above, it can be concluded that the using fairy tales can motivate students in reading English material.AbstrakTujuan penelitian ini adalah untuk menemukan motivasi mahasiswa dalam membaca materi bahasa Inggris dengan menggunakan dongeng. Pada penelitian ini, peneliti menggunakan metode deskriptif. Populasi penelitian ini adalah siswa kelas VIII di SMP Negeri 3 Polewali tahun ajaran 2012/2013 yang terdiri dari 3 kelas dengan jumlah siswa sebanyak 124. Jumlah siswa yang banyak maka peneliti menggunakan metode random sampling. Peneliti hanya mengambil sebanyak 20 siswa sebagai responden. Hal tersebut dilihat dari data perolehan angket mulai tebel 1 sampai table 19 yang memperlihatkan tingkat rata-rata siswa dengan pilihan sangat tertarik sebanyak 43 persen dan tertarik sebanyak 48 persen. Jadi totalnya sebesar 91 persen. Artinya, siswa yang memilih jawaban sangat tertarik dan tertarik lebih dari 50 persen. Berdasarkan data yang telah dikumpulkan tersebut, maka dapat disimpulkan bahwa dengan menggunakan dongeng dapat memotivasi siswa dalam membaca materi bahasa Inggris.